ĐÁNH GIÁ BIẾN ĐỘNG TRẠNG THÁI CHỨC NĂNG CƠ THỂ TRƯỚC VÀ SAU KHI BAY CỦA PHI CÔNG QUÂN SỰ LÁI MÁY BAY PHẢN LỰC SU-30 - Nguyễn, Hồng Quang; Bùi, Thị Hương; Trần, Thị Nhài; Nguyễn, Mậu Thạch; Lê, Văn Quang; Nguyễn, Thị Thùy Linh; Nguyễn, Văn Thắng; Ngô, Văn Hiệu (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF CHANGES OF THE BODY FUNCTION STATUS BEFORE AND AFTER FLIGHT OF MILITARY PILOTS FLYING SU-30 AIRCRAFTThe aim of this study is to analyze the measurement data on the Ritm - MET system at the time right before and after flight of 30 military pilots flying the Sukhoi Su-30 aircraft in Vietnam to evaluate the fluctuations in the functional state of the body. The pilots were tested for the following parameters: changes in cardiovascular function indicators; results of performing neuromotor tests; level of body function status. The results showed that the functional state of military pilots after flying had a strong fluctuation reflected in the increase of indicators: heart rate intensity, blood pressure, and TI-regulatory stress index and Hildebrandt index. In addition, the functional state of the sensory and motor systems under the control of the central nervous system of the pilots after flying was also impaired as shown by the increase in average reaction time and false reflex rate, decreased hit rate in tests as well as increased fatigue index.